Comparison the Diagnostic Value of Doppler Ultrasonography to Biopsy, in Evaluation of Post-transplant Complications and Kidney Function - Hajipour, Roja; Morteza Bagheri, Seyed; Ghadamzadeh, Mostafa; Sadeghi, Pedram; Vahedifard, Farzan; Salmanipour, Alireza (Journal of Organ Transplantation, 2022)
Background Doppler ultrasonography can evaluate vascular and renal parenchymal disorders. In this study, color Doppler patterns in transplanted kidneys were compared with histological diagnosis to develop diagnostic models for transplanted kidney failure. Method 45 kidney transplant patients participated in this prospective study (16 suffered acute tubular necrosis (ATN), and 29 had transplant rejection). All patients had color-Doppler ultrasonography to measure kidney parameters and Doppler indices. Serum creatinine levels also assessed the transplanted kidney's function. Result Ultrasound showed a significant difference between the two groups in iliac and interlobar PSV. The ROC analysis showed a high diagnostic value of the iliac artery PSV, in distinguishing ATN from kidney transplant rejection. Serum creatinine level correlated directly with transplanted kidney volume, renal cortical thickness, and transplanted kidney length, and inversely with interlobar artery PSV and EDV. In graft rejection patients, the only significant inverse correlation was found between serum creatinine level and PSV of the iliac artery and EDV of the intrelobar artery. Discussion and conclusion The iliac artery PSV can differentiate between ATN and rejection after renal transplantation. Evaluation of renal metric parameters along with PSV and EDV of the interlobar artery (in patients with ATN) and iliac artery and interlobar artery (in transplant rejection) help determine renal dysfunction.
Keywords: Doppler ultrasonography; post-transplant; kidney function; biopsy